Incidence of Dementia in Elderly Latin Americans: Results of the Maracaibo Aging Study (2018)
ABSTRACT: INTRODUCTION—There are few longitudinal studies of dementia in developing countries. We used longitudinal data from the Maracaibo Aging Study (MAS) to accurately determine the age-and sex-specific incidence of dementia in elderly Latin Americans. METHODS—The DSM IV-R was used to diagnose dementia, which was classified as Alzheimer’s disease (AD), vascular dementia (VaD), or other. Age- and sex-specific incidence was estimated as the number of new cases of dementia divided by person-years of follow-up (p-y). RESULTS—The incidence of all dementia diagnoses was 9.10 per 1000 p-y (95% CI 7.13–11.44;8026 total p-y), 5.18 for AD (95% CI 3.72–7.03; 7916 total p-y), and 3.35 for VaD (95% CI 2.19–4.91;7757 total p-y). DISCUSSION—Among MAS participants under 65 years of age, the incidence of dementia was higher than that of US whites. Among individuals over 65 years of age, the incidence was comparable to the mean of previous incidence estimates for other populations worldwide.